ANALYSIS OF ONLINE LEARNING METHODS ON THE EFFECTIVENESS OF CHEMISTRY LEARNING DURING THE COVID-19 PANDEMIC ON MUHAMMADIYAH SENIOR HIGH SCHOOL 3 BATU STUDENTS - Sakif, Salman (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
This study aims to reveal the differences in the effectiveness of chemistry learning before and after using online learning methods during the Covid 19 pandemic for Muhammadiyah Senior High School 3 Batu students. This type of research is expo facto using a quantitative approach. The research population was class 12th grade student from Science 2 and Science 3 of Muhammadiyah Senior High School 3 Batu Students with a total of 62 people. Samples were taken using a non-random sampling technique, namely purposive sampling with an analytical formula. In this analysis method, using 2 stages, namely univariate analysis and bivariate analysis. The findings reveal that before online learning more students got good results on chemistry, with the average score of 89,9. Meanwhile, after online learning was 88,2. Therefore, from the results of the bivariate test analysis showed that there were differences in the effectiveness of learning chemistry before and after online learning for students.